Biological Evaluation of DNA Biomarkers in a Chemically Defined and Site-Specific Manner - Ke Bian; James C. Delaney; Xianhao Zhou; Deyu Li (Toxics, 2019)
As described elsewhere in this Special Issue on biomarkers, much progress has been made in the detection of modified DNA within organisms at endogenous and exogenous levels of exposure to chemical species, including putative carcinogens and chemotherapeutic agents. Advances in the detection of damaged or unnatural bases have been able to provide correlations to support or refute hypotheses between the level of exposure to oxidative, alkylative, and other stresses, and the resulting DNA damage (lesion formation). However, such stresses can form a plethora of modified nucleobases, and it is therefore difficult to determine the individual contribution of a particular modification to alter a cell’s genetic fate, as measured in the form of toxicity by stalled replication past the damage, by subsequent mutation, and by lesion repair. Chemical incorporation of a modification at a specific site within a vector (site-specific mutagenesis) has been a useful tool to deconvolute what types of damage quantified in biologically relevant systems may lead to toxicity and/or mutagenicity, thereby allowing researchers to focus on the most relevant biomarkers that may impact human health. Here, we will review a sampling of the DNA modifications that have been studied by shuttle vector techniques.